Mortality update of cellulose fiber production workers. - Lanes, S. F.; Rothman, K. J.; Dreyer, N. A.; Soden, K. J. (Scandinavian Journal of Work, Environment & Health, 1993)
Mortality ascertainment was extended through 1990 for a cohort of 1271 workers involved in the production of cellulose triacetate fiber at a plant in Rock Hill, South Carolina. Each subject was employed for at least three months between 1 January 1954 and 1 January 1977 in jobs that entailed exposure to the highest concentrations of methylene chloride. Median exposures in 1977 ranged from 140 to 745 ppm (8-h time-weighted average). The observed numbers of deaths from specific causes were compared with the expected numbers of deaths computed from rates in York County, South Carolina. For most causes of death, there was little if any association with employment. Among causes of particular interest, no new deaths were observed from cancer of the liver and biliary tract, although the excess from the earlier study persisted (4 observed, 1.34 expected). No excess mortality was observed for cancer of the pancreas (2 observed, 2.42 expected) or for ischemic heart disease (43 observed, 47.8 expected).